Figure 3 in A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species - Wilbert, Norbert; Song, Weibo (Zenodo, 2008)
Figure 3. Pseudocohnilembus persalinus (A), Euplotes vannus (B, C), Metaurostylopsis marina (D, E) and Holosticha apodiademata nov. spec. (F, G) after silver-nitrate (A) and protargol impregnation (B–G). (A) Ventral view of silverline system, arrow marks the small membranelle 3. (B, C) Ventral and dorsal view of the same specimen, arrow in B indicates the paroral membrane. (D, E) Ventral and dorsal views of the same specimen, doublearrowheads mark the posterior end of the ventral row, which is continued by the short midventral rows, while the arrow indicates the buccal cirrus. (F, G) Ventral and dorsal view of the same specimen, arrow marks the big gap between the two parts of the adoral zone. AZM, adoral zone of membranelles; CC, caudal cilia (in A) or caudal cirri (in B); BC, buccal cirrus; Cs, cytostome; CVP, contractile vacuole pore; CyP, cytopyge; DK, dorsal kineties; FC, frontal cirri; FTC, frontoterminal cirri; FVC, frontoventral cirri; M1, M2, membranelles 1 and 2; Ma, macronucleus; MC, marginal cirri; MVR, midventral rows; PM, paroral membrane; SKn, last somatic kinety; TC, transverse cirri. Scale bars: 25 Mm (A); 40 Mm (B–E); 50 Mm (F, G). : Published as part of Wilbert, Norbert & Song, Weibo, 2008, A further study on littoral ciliates (Protozoa, Ciliophora) near King George Island, Antarctica, with description of a new genus and seven new species, pp. 979-1012 in Journal of Natural History 42 (13-14) on page 987, DOI: 10.1080/00222930701877540, http://zenodo.org/record/5219160